Certification of Accountants Profession - Koczar, Joanna (Certyfikacja zawodu księgowego, 2010)
Nineties of the 21st century brought first rules regarding profession practiced by accountants. Early regulations were made on the level of decrees and in the passing years were replaced by records in balance law. Still those regulations concern only accountants who practice their profession by taking commissions from outside (outsourcing of accountancy and tax records). The attempt to certificate profession of an accountant (concerning all accountants) undertaken by The Accountants Society in Poland arouses comprehensible curiosity and some doubts.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 41-46
Keywords: certification; Accountants Society in Poland; level of decrees